Incidental detection of stomach cancer in surgical piece of gastric sleeve: case report and literature review (Basic Health sciencies journal, 2024)
Introduction. Gastric cancers, impose a considerable global health burden in the absence of early detection strategies, leading to poor prognosis especially in late stages. Clinical case. We present the case of a patient with a history of metabolic syndrome, with preoperative endoscopy that reported hiatal hernia, gastropathy and chronic antral gastritis. Subsequently she was treated with gastric sleeve, without complications, with report of intraoperative histological piece of stomach that reports adenocarcinoma in the gastric body wall as incidental finding. Results. Detection of gastric oncologic pathology was achieved, which allowed timely management, directly impacting the quality and survival of the patient. Conclusion. This finding underscores the importance of performing upper endoscopy in all patients undergoing bariatric surgery, to rule out premalignant and/or early tumor lesions. Especially, in those patients who will undergo gastric bypass, since there will be a residual stomach whose endoscopic approach will be complex. Likewise, the need to send the surgical specimen for pathological study is emphasized.
Keywords: gastrointestinal; bariatric surgery; gastric cancer; late diagnosis; adenocarcinoma; endoscopy; biopsy